Vascular trauma in the Amazon - the challenge of great distances - ADENAUER MARINHO DE OLIVEIRA GÓES JUNIOR; ALLAN DIAS VASCONCELOS RODRIGUES; FÁBIO BRITO BRAGA; MARISETH CARVALHO DE ANDRADE; SIMONE DE CAMPOS VIEIRA ABIB (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACTObjective:to evaluate the incidence of unfavorable outcomes in vascular trauma patients and their possible correlation to the distance between the city where the injury was sustained and the hospital where the patient received definitive treatment.Methods:descriptive and retrospective study. Data were collected from medical records of patients submitted to surgical procedures for arterial or venous injuries from February 2011 to February 2013 at the only trauma center providing vascular surgery in a vast area of the Amazon region. Trauma date, patient gender and age, mechanism and anatomic topography of injury, surgical management, need for surgical re-intervention, hospitalization period, postoperative complications, mortality and limb amputation rates were analyzed. The incidence of unfavorable outcomes was assessed according to the distance between the city where the vascular injury was sustained and the trauma center.Results: One hundred seventy-three patients with 255 vascular injuries were analyzed; 95.95% were male (p<0.05), mean age of 28.92 years; 47.4% were caused by firearm projectiles (p<0.05); topographic distribution: 45.66% lower limbs (p<0.05), 37.57% upper limbs, 6.94% abdominal, 5.2% thoracic and 4.62% were cervical vascular injuries; 51.42% of patients required hospitalization for seven days or less (p<0.05); limb amputation was necessary in 15.6% and the overall mortality was 6.36%.Conclusion:distances greater than 200Km were associated to longer hospitalization period; distances greater than 300Km were associated to increased limb amputation probability; severe vascular trauma have an increased death probability when patients need to travel more than 200Km for surgical treatment.